Analysis of the process of formation of N-nitrosodimethylamine in brewer’s malt - Shutyuk, Vitaliy; Bessarab, Alexander; Haralanova, Temenuzhka; Vasylenko, Sergei (My University, 2014)
The article deals with the issues of carcinogenic substances formation in the manufacture of beer. It is shown that the basic technological process, that influences the N-NDMA accumulation in beer, is brewer's malt drying. The determining factor, influencing the N-NDMA content in malt, is the concentration of nitrogen dioxide at the entrance to malt layer. In the course of research, drying conditions typical for dryers of «Latvian Academy of Agriculture» type, one-deck dryers and apparatuses on malt manufacturing in combined way were secured. The measuring of nitric oxides was carried out by the means of gas- analyzer of 645 HL 20 type, the principle of operation of which is based on chemiluminescent method of determination of nitric oxide. More intensive absorption of nitrogen dioxide were observed during the first stage (constant speed) of drying due to the large number of free moisture presence in malt – a good nitrogen dioxide absorbent. The concentration of nitrogen dioxide in the drying agent has the greatest impact on intensification of N-NDMA formation processes in malt, that is recorded in all experiments. That is why in order to achieve guaranteed quality of the product, one should establish the limit of concentration of NDMA in malt equaling 15 mcg/kg. Drying of malt with drying agent with concentration of nitric dioxide up to 0,4 mg/m3 guarantees concentration of NDMA lower than this limit. This concentration should be limiting in the field of development of modern heating vent systems.
Keywords: N-nitrosodimethylamine; drying; malt; drying agent; N-нитрозодиметиламин; сушка; солод; сушильный агент; N-нітрозодиметиламін; сушіння; сушильний агент; кафедра теплоенергетики та холодильної техніки; кафедра технології консервування